Synergizing Professional Competence and Islamic Ethics in Human Resource Performance Appraisal - Rahmawati; Hamdi Usman; Ahyar (Managere: Indonesian Journal of Educational Management, 2025)
This research aims to explore the technique of human resource performance assessment in Islamic educational institutions, with an emphasis on the integration between professionalism and Islamic values, such as trust, itqan, and justice. Using a descriptive qualitative approach in the design of multi-case studies. Data were collected through in-depth interviews, participatory observation, and document analysis. The results show that Islamic educational institutions have developed various assessment techniques, including classroom observation, self-assessment, portfolios, 360-degree evaluations, and digital KPIs, which are not only administratively oriented but also focus on the learning process and the work character of teachers. The findings also reveal macro-level (non-standard regulations, budget, and technology limitations) and micro-level (low evaluative literacy, individual resistance) factors that hinder the effectiveness of assessments. Participatory communication has proven crucial in building a fair, transparent, and ethical evaluative culture. This research contributes to the literature on Islamic human resource management by offering contextual and multidimensional assessment models, as well as confirming the importance of synergy between professional evaluation and spiritual coaching in Islamic education governance.